Drug administration: errors committed by nursing professionals and adopted conducts - Marcus Vinicius da Rocha Santos da Silva; Francidalma Soares Sousa Carvalho Filha; Tairo Barros Branco; Jessielly Taís Ferreira Guimarães; Najra Danny Pereira Lima; Anne Karollyne Castro Alves (Universidade Federal de Santa Maria, 2018)
Aim: to analyze behaviors that must be adopted by nursing professionals and managers so that the occurrence of errors in medication administration decreases and to identify errors made by nursing professionals regarding medication administration. Method: descriptive exploratory quantitative study carried out with 162 nursing professionals who work in a hospital in a municipality in Maranhão, Brazil. Data were collected from March to May 2015 and analyzed by descriptive statistics. The Chi-square test was used to analyze the association between variables. Results: training and qualification were considered by 84% of the workers as a priority conduct to be adopted by the management so that the occurrence of errors decreases. It was verified that 19.6% of the professionals have already made mistakes, considering that incorrect medication and inadequate dilution were the most cited failures. Conclusion: To know the causing factors for errors in drug administration is essential for preventive measures to be developed.